2013 IEEE Symposium on Computational Intelligence in Vehicles and Transportation Systems (CIVTS) 2013
DOI: 10.1109/civts.2013.6612288
|View full text |Cite
|
Sign up to set email alerts
|

Data compression techniques for urban traffic data

Abstract: Abstract-With the development of inexpensive sensors such as GPS probes, Data Driven Intelligent Transport Systems (D 2 ITS) can acquire traffic data with high spatial and temporal resolution. The large amount of collected information can help improve the performance of ITS applications like traffic management and prediction. The huge volume of data, however, puts serious strain on the resources of these systems. Traffic networks exhibit strong spatial and temporal relationships. We propose to exploit these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…However, no analysis in terms of reconstruction efficiency of NMF was provided. In a related study, we compared the reconstruction efficiency of different low-dimensional models which were obtained from matrix and tensor based subspace methods for a network comprising of around 6000 road segments [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, no analysis in terms of reconstruction efficiency of NMF was provided. In a related study, we compared the reconstruction efficiency of different low-dimensional models which were obtained from matrix and tensor based subspace methods for a network comprising of around 6000 road segments [23].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Asif et al applied different subspace methods for compression of traffic speed [11]. These studies showed that subspace methods such as PCA and discrete cosine transform (DCT) can efficiently compress traffic data [11]. However, they fail to provide insight about traffic behavior at specific roads and time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Djukic et al applied PCA on small network with OD pair data [9,10]. In another study, Asif et al applied different subspace methods for compression of traffic speed [11]. These studies showed that subspace methods such as PCA and discrete cosine transform (DCT) can efficiently compress traffic data [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method of representing a road network in a compressed form would be to use principal component analysis (PCA) [25]- [27]. This compressed form is given as basis vectors and latent variables.…”
Section: Introductionmentioning
confidence: 99%